2021
DOI: 10.1172/jci150972
|View full text |Cite
|
Sign up to set email alerts
|

Randomized controlled trial of fractionated laser resurfacing on aged skin as prophylaxis against actinic neoplasia

Abstract: BackgroundThe loss of insulin-like growth factor-1 (IGF-1) expression in senescent dermal fibroblasts during aging is associated with an increased risk of non-melanoma skin cancer (NMSC). We tested how IGF-1 signaling can influence photocarcinogenesis during chronic UVB exposure to determine if fractionated laser resurfacing (FLR) of aged skin which upregulates dermal IGF-1 levels can prevent the occurrence of actinic keratosis (AK) and NMSC. MethodsA human skin/immunodeficient mouse xenografting model was use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(23 citation statements)
references
References 31 publications
2
21
0
Order By: Relevance
“…Consistent with this notion, recent studies by our group xenografted human skin onto immunodeficient mice, and the human skin grafts underwent a chronic UVB carcinogenesis protocol with/without treatment with a topical IGF-1R inhibitor. A 20 week UVB treatment of the skin treated with IGF-1R inhibitor, which would mimic geriatric skin, resulted in formation of actinic neoplastic (AKs/early SCC) lesions, findings not seen in vehicle irradiated skin (20). The data from these studies suggests that defective IGF-1/IGF-1R signaling due to senescent dermal fibroblasts is an important cause of geriatric NMSC.…”
Section: Aging Fibroblast Senescence and Photocarcinogenesismentioning
confidence: 86%
See 3 more Smart Citations
“…Consistent with this notion, recent studies by our group xenografted human skin onto immunodeficient mice, and the human skin grafts underwent a chronic UVB carcinogenesis protocol with/without treatment with a topical IGF-1R inhibitor. A 20 week UVB treatment of the skin treated with IGF-1R inhibitor, which would mimic geriatric skin, resulted in formation of actinic neoplastic (AKs/early SCC) lesions, findings not seen in vehicle irradiated skin (20). The data from these studies suggests that defective IGF-1/IGF-1R signaling due to senescent dermal fibroblasts is an important cause of geriatric NMSC.…”
Section: Aging Fibroblast Senescence and Photocarcinogenesismentioning
confidence: 86%
“…Patients underwent a single treatment of FLR on the upper extremity of aged skin. They were examined at three month postwounding and every six months thereafter for a current 36month follow-up period (20). To determine the effectiveness of FLR in reducing the occurrence of AKs, the ratio of the number of AKs on FLR-treated arms to untreated arms was tracked.…”
Section: Fractionated Laser Resurfacingmentioning
confidence: 99%
See 2 more Smart Citations
“…In as much as the increased numbers of senescent fibroblasts found in aged skin result in a significant IGF-1 deficiency, strategies to prevent/and or treat this could have clinical use. In particular, our group recently reported that wounding of geriatric skin with fractionated laser resurfacing which upregulates active fibroblasts could prevent actinic neoplasia including NMSC [48]. Moreover, enzymatic treatment of photoaged skin with agents such as elastase could have beneficial effects [49].…”
Section: Discussionmentioning
confidence: 99%